The effects of low bone mineral density on pain, quality of life and fatigue in patients with epilepsy - AKYÜZ, GÜLSEREN DERYA; MİDİ, İPEK (MARMARA UNIV, FAC MEDICINE, 2021)
Objectives: To investigate the effects of low bone mineral density (BMD) on pain, quality of life (QoL), and fatigue in epileptic patients who use anticonvulsants. Patients and Methods: Epileptic patients aged 18 years or older who use anticonvulsant drugs were recruited into the study. Demographic and clinical features were recorded, including the duration of epilepsy, number of anticonvulsants used, previous fracture history and BMD scores. The functional parameters included back pain measured with the visual analogue scale (VAS) and brief pain inventory (BPI) scale, QoL assessed with the Qualeffo-41 questionnaire, and fatigue assessed with the fatigue severity scale (FSS). Results: Of the 100 patients screened for inclusion in the study, 63 epileptic patients met the inclusion criteria. The mean age and mean disease duration of all participants was 39.5 (+/- 11.2) and 19.3 (+/- 11.6) years, respectively. The median scores for VAS back pain, VAS low back pain, Qualeffo-41, FSS, pain severity, and pain interference (BPI) were significantly higher in patients with secondary osteoporosis compared to patients with normal BMD. There were significant correlations between lumbar spinal BMD and VAS back pain (rho = - 0.58, p < 0.0005), BPI pain severity (rho = - 0.56, p < 0.0005), BPI pain interference (rho = - 0.52, p < 0.0005), Qualeffo-41 (rho = - 0.56, p < 0.0005), and FSS (rho = - 0.41, p = 0.001). Conclusion: Epileptic patients suffering from low BMD showed increased pain, fatigue and impaired QoL. Therefore, BMD measurement should be recommended for the evaluation and management of epileptic patients.
Keywords: Epilepsy; Quality of life; Bone mineral density; Fatigue; Pain; BODY-MASS INDEX; ANTIEPILEPTIC DRUGS; EUROPEAN FOUNDATION; TURKISH VERSION; OSTEOPOROSIS; FRACTURE; RISK; PATHOPHYSIOLOGY; QUESTIONNAIRE; WOMEN